2014
DOI: 10.1155/2014/605894
|View full text |Cite
|
Sign up to set email alerts
|

High Isolation Single-Pole Four-Throw RF MEMS Switch Based on Series-Shunt Configuration

Abstract: This paper presents a novel design of single-pole four-throw (SP4T) RF-MEMS switch employing both capacitive and ohmic switches. It is designed on high-resistivity silicon substrate and has a compact area of 1.06 mm2. The series or ohmic switches have been designed to provide low insertion loss with good ohmic contact. The pull-in voltage for ohmic switches is calculated to be 7.19 V. Shunt or capacitive switches have been used in each port to improve the isolation for higher frequencies. The proposed SP4T swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The dimensions of CPW are specified in Table 1. If C is the capacitance per unit length of line l and C 0 is the capacitance per unit length in the absence of the dielectric layer, then the effective permittivity μ eff for CPW is approximated by using: (9) where; K is the complete elliptical integral of the first kind, and the values of k and k' depend on the geometry configuration of the line and are demonstrated in [11].…”
Section: Equivalent Circuit Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The dimensions of CPW are specified in Table 1. If C is the capacitance per unit length of line l and C 0 is the capacitance per unit length in the absence of the dielectric layer, then the effective permittivity μ eff for CPW is approximated by using: (9) where; K is the complete elliptical integral of the first kind, and the values of k and k' depend on the geometry configuration of the line and are demonstrated in [11].…”
Section: Equivalent Circuit Modelingmentioning
confidence: 99%
“…This paper presents a compact and capacitive/shunt RF MEMS switch for Q-band operation [9]. Being a compact switch, this switch shows prominent performance in the higher frequency region.…”
Section: Introductionmentioning
confidence: 99%
“…CORE TECHNOLOGIES There are many industrial grade tools for simulation depending on the problems. Now-a-days, tools are developed that we can also couple the physics from different domains for analysis [4], [13]. Modeling tools provides an environment for engineers in which they can design, analyse/simulate, compare the results and optimise various factors depending on the type of application [14].…”
Section: Impact Of Research Tools On Education Andmentioning
confidence: 99%
“…RF MEMS switches have huge advantage including; excellent isolation, low insertion loss, negligible power consumption, very compact structure, low cost of manufacturing [20]. But these tiny intelligent devices suffer from reliability issues including stiction and high voltage requirements [13], To overcome these problems, researchers and designers has to model and analyse the issues first and then optimise the design accordingly. In this case study, we have reported that how FEM is useful in estimating the stress gradient to help determining how the membrane of RF MEMS can handle stress for reliable operation [5].…”
Section: Case Study II -Finite Element Modeling For Rf-memsmentioning
confidence: 99%
“…The RF performances for the device in both switching states are extracted by S-parameters. The data of the Smatrix is computed for the 20-100 GHz frequency range [16]. Usually isolation, return loss in OFF state, insertion loss, and return loss in ON state are all required to examine the performance of switch in the RF region.…”
Section: Rf Performance Analysismentioning
confidence: 99%